Factors associated with dental anxiety in patients treated at an integrated dental clinic: a cross-sectional study - Chauca-Bajaña, Luis; Pérez-Jardón, Alba; Carpio-Cevallos, Carlos; Ordoñez Balladares, Andrea; Proaño-Yela, Patricio; Velásquez Ron, Byron; Siguencia Suarez, Leonardo Javier; Romo Olvera, Carla Verenice; Orellana Guerrero, Diana; Pérez-Sayáns, Mario (Frontiers in Oral Health, 2025)
BackgroundDental anxiety is a widespread issue that significantly impacts oral health behaviors, often leading individuals to postpone or avoid dental care. This avoidance can result in more complex and invasive treatments. This study aimed to evaluate the levels of dental anxiety and associated factors among patients attending the dental clinic at the University of Guayaquil, Ecuador.Materials and methodsA total of 389 patients were assessed using three validated instruments: the Modified Dental Anxiety Scale (MDAS), the Dental Anxiety Short Scale (SDAI), and the Dental Anxiety and Fear Diagnosis (DAYMO). Statistical analyses included bivariate tests and correlation analyses using Spearman's rho and Pearson's chi-square tests.ResultsAmong the participants, 63.8% were female and 36.3% were male. Women reported significantly higher levels of anxiety across all assessment tools (p < 0.05). Based on the SDAI, 47% of patients exhibited moderate to severe anxiety, whereas 19% reported high anxiety levels on the MDAS. The DAYMO instrument revealed that 51.2% of participants experienced mild anxiety, and 27.8% had moderate anxiety. Common anxiety triggers included fear of pain, past negative dental experiences, and concerns about needles or oral hygiene practices.ConclusionsDental anxiety was prevalent among patients, particularly among women, with most experiencing mild to moderate levels. These findings underscore the importance of addressing psychological factors in dental care settings to improve patient experience and outcomes.